2022
DOI: 10.15585/mmwr.mm7136a1
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Sexually Transmitted Infections Among Persons with Monkeypox — Eight U.S. Jurisdictions, May 17–July 22, 2022

Abstract: and city or county jurisdictions independently funded for HIV surveillance: California (including Los Angeles County and San Francisco), District of Columbia, Georgia, Illinois (including Chicago), and New York (excluding New York City).preventive care should be routinely offered to persons evaluated for monkeypox, with linkage to HIV care or HIV preexposure prophylaxis (PrEP) as appropriate.Eight health departments matched probable and confirmed cases of monkeypox † diagnosed through July 22, 2022, and occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 6 publications
8
151
1
2
Order By: Relevance
“…Since March 2020, the world has been faced with the burden of the COVID-19 pandemic, which is now coupled with MPXV for a specific population, that is especially MSM people [ 12 , 22 ]. In the United States, most MPXV cases have occurred among MSM who have a higher prevalence of HIV and STIs than the general population [ 22 ]. MPXV infection most often begins with a fever, which is frequently high and accompanied by headaches, body aches and asthenia.…”
Section: Discussionmentioning
confidence: 99%
“…Since March 2020, the world has been faced with the burden of the COVID-19 pandemic, which is now coupled with MPXV for a specific population, that is especially MSM people [ 12 , 22 ]. In the United States, most MPXV cases have occurred among MSM who have a higher prevalence of HIV and STIs than the general population [ 22 ]. MPXV infection most often begins with a fever, which is frequently high and accompanied by headaches, body aches and asthenia.…”
Section: Discussionmentioning
confidence: 99%
“…Such an association with an existing healthcare engagement was also found in a United States study, which showed a higher vaccination rate among MSM on HIV PrEP or who were recently tested for STIs [ 14 ]. Increasing HIV prevalence among MPX cases over time suggests that MPX might be increasingly transmitted among networks of persons with HIV infection [ 15 ]. The prioritisation of people linked with healthcare might be beneficial, especially with the current shortage of vaccines, as they are easier to reach and might be an important group in transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Many MSM face barriers to accessing HIV services because of stigma, homophobia, racism, xenophobia, poverty, and limitations in health insurance †††† ( 1 , 2 ). Successful response interventions should aim to eliminate these barriers, quickly close service gaps, and address existing and emerging syndemics affecting MSM, including sexually transmitted infections and monkeypox ( 9 ). When mobilized effectively, strategies that engage communities, improve prevention services, and strengthen linkage to care can address the needs of persons in HIV clusters.…”
Section: Discussionmentioning
confidence: 99%